Chinese EFL Learners’ Decision-making While Evaluating Peers’ Texts - Ma, Jingjing (International Journal of English Studies, 2010)
Approaching peer review from a process and contextualized perspective, this exploratory case study investigates two Chinese EFL learners’ decision-making patterns while evaluating peers’ texts in an online peer review and factors influencing these patterns. Detailed qualitative case study data were collected through think-aloud protocols, stimulated recall, semi-structured interviews, classroom observation and document analysis. Analyses indicate that the two learners with higher level of English writing proficiency to a certain extent illustrated contrasting patterns of decision-making, and yet both prioritized specific aspects of peers’ texts. Student-related factors such as perceptions of good English expository writing shaped by previous learning and assessment experiences of English (or Chinese) writing, type of writing task and weaknesses of student text interacted with one another to influence the participants’ decision-making patterns. Pedagogical implications for the findings are discussed.